Battery heat insulation sheet, manufacturing method thereof, and battery module comprising the same
Patent Information
- Application Number
- JP2024092196
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-16
- Filing Date
- 2024-06-06
- Publication Date
- 2025-02-28
AI Technical Summary
【0029】 一実施形態に係るバッテリー断熱シートは、断熱性及び耐久性に優れており、エアロゲルによってコートされている形態を有するエアロゲル層を含むことによって断熱性及び圧縮特性に優れ、製造工程コストが低く、且つ製造過程又は実使用時にエアロゲルの粉塵発生を防止することができる。
Smart Images

Figure 2025027965000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a battery insulation sheet, a manufacturing method thereof, and a battery module including the same. [Background technology]
[0002] Secondary batteries are power storage systems that provide excellent energy density by converting electrical energy into chemical energy and storing it. Unlike primary batteries, which cannot be recharged, secondary batteries can be recharged, and are widely used in IT devices such as smartphones, cellular phones, laptops, and tablet PCs. In recent years, interest in electric vehicles has increased to prevent environmental pollution, and high-capacity secondary batteries are being adopted for electric vehicles. Such secondary batteries are required to have characteristics such as high density, high output, and stability.
[0003] On the other hand, when a battery contains a large number of high-capacity cells such as lithium-ion secondary batteries, there is a risk that one cell may overheat and experience thermal runaway, adversely affecting other adjacent cells, and therefore it is required that adjacent cells are thermally insulated from each other.
[0004] Therefore, conventionally, a plate material or an insulating resin plate is placed between the cells to insulate and heat the adjacent cells.
[0005] The above information disclosed in the Background of the Invention is intended to enhance the understanding of the background of the present invention only, and may therefore include information that does not constitute prior art. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides a battery insulation sheet that can be manufactured through a simple process and has excellent insulation properties, compression characteristics, durability, and low dust properties, a manufacturing method thereof, and a battery module including the same. [Means for solving the problem]
[0007] One embodiment provides a battery insulation sheet having a structure in which a first substrate, an aerogel layer, and a second substrate are sequentially laminated, and both sides of the aerogel layer directly face the adjacent first substrate or the adjacent second substrate, respectively.
[0008] There may be no need to include a separate layer, including an adhesive, between the aerogel layer and the first substrate or the second substrate.
[0009] The aerogel layer can satisfy the following formula 1: 0.1≦PD1≦0.5, PD1=PA / PB (Formula 1)
[0010] In Equation 1, PA is the mass per unit volume of the aerogel layer after a pressure of 0 kN is applied vertically to the aerogel layer (g / cm 3 ) and PB is the mass per unit volume of the aerogel layer after applying a pressure of 5 kN vertically to the aerogel layer (g / cm 3 )
[0011] The aerogel layer can satisfy the following formula 2: 0.1≦PD2≦0.4,PD2=PB / PC (Formula 2)
[0012] In Equation 2, PB is the mass per unit volume of the aerogel layer after a pressure of 5 kN is applied vertically to the aerogel layer (g / cm 3 ), and PC is the mass per unit volume of the aerogel layer after applying a pressure of 20 kN vertically to the aerogel layer (g / cm 3 )
[0013] Each of the first substrate and the second substrate may include a resin, a metal, an inorganic material other than a metal, or a composite thereof.
[0014] The first substrate and the second substrate may each have an air permeability of 800 sec / 100 cc to 40,000 sec / 100 cc.
[0015] The aerogel layer may include a fibrous support, an aerogel, and a functional material including a binder, a dispersant, or a combination thereof.
[0016] The fibrous support may be one or more fibers selected from the group consisting of natural fibers, silica fibers, glass fibers, ceramic fibers, carbon fibers, graphite fibers, mineral fibers, and polymer fibers.
[0017] The aerogel has a BET specific surface area of 500 m 2 / g~1,000m 2 / g.
[0018] The binder may include a water-based polymeric binder.
[0019] The dispersant may be one or more selected from the group consisting of surfactants and phosphate salts.
[0020] The aerogel layer may contain, relative to the total amount of the aerogel layer, 25% by weight to 60% by weight of the fibrous support, 30% by weight to 70% by weight of the aerogel, and 2% by weight to 15% by weight of the binder.
[0021] The aerogel layer may contain, relative to the total amount of the aerogel layer, 25% by weight to 60% by weight of the fibrous support, 30% by weight to 70% by weight of the aerogel, 2% by weight to 15% by weight of the binder, and 0.1% by weight to 5% by weight of the dispersant.
[0022] The first and second substrates each may have a thickness of 0.01 mm to 5 mm, and the aerogel layer may have a thickness of 1 mm to 10 mm.
[0023] Another embodiment provides a method for manufacturing a battery insulation sheet, the method including: applying an aerogel composition onto a first substrate; laminating a second substrate onto the applied aerogel composition to manufacture a laminate; controlling a thickness of the laminate; and drying the laminate.
[0024] The method for producing the aerogel composition may include mixing a functional material, including a binder, a dispersant, or a combination thereof, with a solvent to produce a solvent mixture, mixing the solvent mixture with an aerogel powder to produce an aerogel mixture, and mixing the aerogel mixture with a fibrous support to produce an aerogel composition.
[0025] The solvent may be one or more selected from the group consisting of polar solvents and non-polar solvents.
[0026] The step of controlling the thickness of the laminate may include controlling the thickness of the laminate by a method of applying pressure using a roller.
[0027] The step of drying the laminate may be performed at a temperature of 25°C to 100°C.
[0028] Yet another embodiment includes a battery module including a plurality of cells and the above-mentioned battery insulation sheets respectively provided between the plurality of cells, wherein the first and second substrates of the insulation sheets are each arranged to face an adjacent cell. Effect of the Invention
[0029] The battery insulation sheet according to one embodiment has excellent insulation properties and durability, and includes an aerogel layer coated with aerogel, thereby providing excellent insulation properties and compression characteristics, reducing manufacturing costs, and preventing the generation of aerogel dust during the manufacturing process or in actual use. [Brief description of the drawings]
[0030] [Figure 1] 1 is a schematic diagram showing a structure of a battery insulation sheet according to an embodiment; [Diagram 2] FIG. 2 is a schematic diagram showing a battery insulation sheet according to an embodiment formed between a plurality of cells. [Diagram 3] FIG. 2 is a schematic diagram showing the structure of a battery insulating sheet in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Although the present invention will be described in detail below so as to be easily understood by those skilled in the art, the present invention may be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein.
[0032] Insulation materials are materials that prevent the flow of heat from a high temperature area to a low temperature area, and are used in refrigerators, freezer warehouses, and buildings as well as in various industrial fields including the aircraft, electronic parts, and automotive industries.
[0033] Such a heat insulating material should have excellent heat insulating performance due to low thermal conductivity, and is also required to have sufficient mechanical strength to maintain such heat insulating performance.
[0034] Meanwhile, aerogel is a transparent or translucent cutting-edge material with a nanoporous structure, and has very low density and low thermal conductivity. As such, it not only has great potential as an insulating material, but is also considered a highly efficient super-insulating material that can be used in a variety of industrial fields.
[0035] Furthermore, the greatest advantage of aerogel is that it exhibits lower thermal conductivity than conventional organic insulation materials such as styrofoam, and that it solves the fatal weaknesses of organic insulation materials, namely, vulnerability to fire and the generation of harmful gases during a fire.
[0036] However, in general, aerogel has very low strength, i.e., is easily broken even by a small impact due to its high brittleness, and is difficult to process into a very thin thickness and shape. Therefore, despite its excellent thermal insulation properties, it is very difficult to manufacture a thermal insulation material by using aerogel alone.
[0037] The battery insulation sheet according to one embodiment has a structure in which a first substrate, an aerogel layer, and a second substrate are sequentially laminated, and both sides of the aerogel layer may directly face the adjacent first substrate or the adjacent second substrate, respectively.
[0038] The battery insulation sheet formed by the above structure has excellent insulation properties, durability, and compression characteristics, has low manufacturing costs, and can prevent aerogel dust generation during the manufacturing process or actual use.
[0039] FIG. 1 is a schematic diagram showing the structure of a battery insulation sheet according to one embodiment.
[0040] Referring to FIG. 1, the battery insulation sheet 100 has a structure including a first substrate 110, an aerogel layer 120 formed on the first substrate 110, and a second substrate 130 formed on the aerogel layer 120, and may be formed in a structure in which the first substrate 110, the aerogel layer 120, and the second substrate 130 are sequentially stacked.
[0041] Here, a separate layer including an adhesive may not be included between the aerogel layer and the first or second substrate. Specifically, the battery insulation sheet may be manufactured by the method and conditions described below, so that the battery insulation sheet may be manufactured in a one-step process with a structure in which the first substrate, the aerogel layer, and the second substrate are sequentially laminated without the use of an adhesive.
[0042] The first and second substrates may be made of various materials such as resin, metal, inorganic material other than metal, or composites thereof, and the type of the materials is not limited. The form of the substrate may be a film, thin film, sheet, or the like, and is not particularly limited.
[0043] The resin may be, for example, one or more selected from the group consisting of polyethylene, polypropylene, polystyrene, polyethylene terephthalate, polyepoxy, and polyamide.
[0044] The metal may be, for example, one or more selected from the group consisting of copper, nickel, cobalt, iron, chromium, vanadium, palladium, ruthenium, rhodium, molybdenum, tungsten, iridium, silver, gold, and platinum. When using a substrate made of the above metal material, the substrate may be subjected to anti-corrosion treatment, insulation treatment, etc., as necessary.
[0045] The inorganic material is calcium carbonate (CaCO 3 ), talc, and mica.
[0046] As a specific example, the first substrate and the second substrate may include an inorganic material, and more specifically, may include mica, in which case the heat insulation property and durability of the heat insulation sheet may be improved.
[0047] The first and second substrates may each include an inorganic material having an air permeability of 800sec / 100cc to 40,000sec / 100cc. For example, the air permeability can be adjusted according to the thickness of the substrate, and may be 1,000sec / 100cc to 30,000sec / 100cc, 1,000sec / 100cc to 3,000sec / 100cc, 6,000sec / 100cc to 10,000sec / 100cc, 10,000sec / 100cc to 30,000sec / 100cc, or 20,000sec / 100cc to 30,000sec / 100cc. Here, the air permeability was measured using an air permeability tester (Asahi Seiko OKEN Type Air permeation tester model EGO1-55-1MR) according to a measurement method based on ISO 5635-5, and was expressed as the time (sec) it took for 100 cc of air to pass through. By forming an aerogel layer between a first substrate containing an inorganic material having an air permeability within the above range and a second substrate, it is possible to obtain excellent binding strength between the first substrate and the second substrate and the aerogel layer without an adhesive layer. In addition, when an adhesive layer is formed, there is a problem that the adhesive component is weak against heat and is easily broken at high temperatures of 200°C or higher, but the battery insulation sheet according to one embodiment does not include an adhesive layer and has excellent stability at high temperatures.
[0048] The thickness of each of the first and second substrates may be 0.01 to 5 mm, 0.05 to 3 mm, or 0.1 to 1 mm. By forming an aerogel layer between the first and second substrates having thicknesses within the above ranges, a battery insulation sheet having excellent heat insulation properties, durability, and dust resistance can be obtained.
[0049] In one embodiment, the aerogel layer can satisfy the following formula 1: 0.1≦PD1≦0.5, PD1=PA / PB (Formula 1)
[0050] In Equation 1, PA is the mass per unit volume of the aerogel layer after a pressure of 0 kN is applied vertically to the aerogel layer (g / cm 3) and PB is the mass per unit volume of the aerogel layer after applying a pressure of 5 kN vertically to the aerogel layer (g / cm 3 ) The value of PD1 may be, for example, 0.1 to 0.5, 0.1 to 0.4, or 0.2 to 0.3. When the value of PD1 is within the above range, the durability against external impact or pressure when mounting the module is excellent.
[0051] The aerogel layer can satisfy the following formula 2: 0.1≦PD2≦0.4,PD2=PB / PC (Formula 2)
[0052] In Equation 2, PB is the mass per unit volume of the aerogel layer after a pressure of 5 kN is applied vertically to the aerogel layer (g / cm 3 ), and PC is the mass per unit volume of the aerogel layer after applying a pressure of 20 kN vertically to the aerogel layer (g / cm 3 ) The value of PD2 may be, for example, 0.1 to 0.4, 0.15 to 0.35, or 0.25 to 0.35. It was confirmed that when the value of PD2 is within the above range, the durability of the internal cell against swelling is excellent.
[0053] The above values of PD1 and PD2 may represent the compression density of the aerogel layer, and thus the degree of vacant space inside the aerogel layer due to the applied pressure can be confirmed. In one embodiment, the aerogel layer has a large vacant space inside due to the fibrous support uniformly distributed by the manufacturing method described below and the aerogel present in the form of a coating on the surface of the fibrous support, and may have a value of PD1, a value of PD2, or values of PD1 and PD2 within the above range. In this way, by satisfying the value of PD1, the value of PD2, or the value of PD1 and PD2, durability against external impact or internal swelling, heat insulation, compression properties, etc. are excellent.
[0054] In one embodiment, the aerogel layer may include a fibrous support, an aerogel, and a functional material including a binder, a dispersant, or a combination thereof.
[0055] The thickness of the aerogel layer may be 1 mm to 10 mm, 1 mm to 5 mm, or 1 mm to 3 mm. By forming an aerogel layer on a substrate having a thickness within the above range, a heat insulating sheet having excellent heat insulating properties and compression characteristics can be produced.
[0056] In one embodiment, the fibrous support is included in the aerogel layer, thereby improving the durability of the battery insulation sheet.
[0057] The fibrous support may include fibers used as supports for conventional heat insulating materials. For example, the fibrous support may be one or more selected from the group consisting of natural fibers, silica fibers, glass fibers, ceramic fibers, carbon fibers, graphite fibers, mineral fibers, and polymer fibers. As a specific example, the fibrous support may include glass fibers, but is not limited thereto.
[0058] The natural fibers may be, for example, one or more selected from the group consisting of hemp, jute, flax, coir, hemp, and cellulose.
[0059] The mineral fibers may be, for example, one or more mineral fibers selected from the group consisting of basalt, wollastonite, alumina, silica, slag, and rock.
[0060] The polymer fiber may be at least one selected from the group consisting of nylon, polyimide, polyamide, polybenzimidazole, polybenzoxazole, polyamideimide, polyethyleneterephthalate, polybutyleneterephthalate, polyester, polyethylene (PE), and polypropylene (PP). As a specific example, the polymer fiber may include at least one of polyimide, polyamide, and polybenzimidazole, but is not limited thereto.
[0061] The fibrous support may be, for example, in the form of wool or chopped strands, but is not limited thereto.
[0062] The diameter of the fibrous support may be, for example, 0.1 μm to 20 μm, 0.1 μm to 15 μm, 0.1 μm to 5 μm, 1 μm to 15 μm, or 3 μm to 10 μm. By including a fibrous support having a diameter within the above range, the structure of the aerogel layer can be made stronger, and the production cost can be reduced.
[0063] The length of the fibrous support may be, for example, 50 μm to 1000 μm, 70 μm to 800 μm, or 100 μm to 600 μm. By including a fibrous support having a length within the above range, the aerogel layer can be formed firmly and durability can be improved.
[0064] The content of the fibrous support may be 5% by weight to 70% by weight, 25% by weight to 60% by weight, or 30% by weight to 50% by weight, based on the total amount of the aerogel layer. A battery insulation sheet including an aerogel layer containing a fibrous support within the above range can have improved durability.
[0065] In one embodiment, the aerogel has a BET specific surface area of 500 m 2 / g~1,000m 2 For example, the aerogel may have a BET specific surface area of 500 m2 / g to 950 m2 / g. 2 / g, 550m2 / g~950m 2 / g, or 600m 2 / g~900m 2 By including an aerogel having a BET specific surface area value within the above range, it is possible to provide a heat insulating sheet capable of effectively preventing heat transfer and heat propagation between a plurality of cells.
[0066] The average particle size (D50) of the aerogel may be 5 μm to 200 μm, 10 μm to 100 μm, or 20 μm to 50 μm. By including an aerogel having an average particle size within the above range, the heat insulating properties can be improved and the heat transfer between the multiple cells can be delayed.
[0067] The content of the aerogel may be 10% by weight to 90% by weight, 30% by weight to 70% by weight, or 40% by weight to 60% by weight based on the total weight of the aerogel layer. When the battery insulation sheet containing the aerogel in the above range is manufactured, the insulation property can be improved.
[0068] In one embodiment, the binder may include a water-based polymer binder. For example, the water-based polymer binder may be at least one selected from the group consisting of a water-based polymer, an anionic water-soluble polymer, a cationic water-soluble polymer, and a water-dispersible polymer.
[0069] The aqueous polymer may be, for example, at least one selected from the group consisting of polyvinyl alcohol, polyethylene oxide, polyacrylamide, and polyvinylpyrrolidone, but is not limited thereto.
[0070] The anionic water-soluble polymer may be at least one selected from the group consisting of polymers having functional groups of carboxylic acid, sulfonic acid, sulfate, phosphate, and salts thereof. For example, the anionic water-soluble polymer may be a polymer having a carboxylic acid group, and a specific example thereof may include, but is not limited to, polymaleic acid.
[0071] The cationic water-soluble polymer may be at least one selected from the group consisting of polymers having functional groups of amine, ammonium, phosphonium, sulfonium, and salts thereof. For example, the cationic water-soluble polymer may be a polymer having an amine group, and a specific example may be at least one selected from the group consisting of polyethylene amine and polyamine, but is not limited thereto.
[0072] The water-dispersible polymer may be at least one selected from the group consisting of water-dispersible polyurethane and water-dispersible polyester, but is not limited thereto.
[0073] The binder may include a water-based polymer and a water-dispersible polymer, for example, a water-based polymer having binder properties as well as dispersion properties, and a water-dispersible polyurethane having fire-resistant properties, and a specific example thereof may include polyvinyl alcohol and water-dispersible polyurethane.
[0074] The weight ratio of the aqueous polymer and the water-dispersible polymer may be 1:1 to 1:5, 1:1 to 1:4, or 1:2 to 1:3. When the weight ratio of the aqueous polymer and the water-dispersible polymer is used in combination within the above range, the heat insulation property, dust resistance, and compressibility of the heat insulation sheet can be further improved as well as the fire resistance and mechanical properties.
[0075] The content of the binder may be 0.5 wt% to 20 wt%, 2 wt% to 15 wt%, or 8 wt% to 15 wt% based on the total amount of the aerogel layer. When the battery insulation sheet is manufactured using an aerogel composition containing a binder within the above range, the dust characteristics of the battery insulation sheet can be improved.
[0076] In one embodiment, the dispersant may be at least one selected from the group consisting of surfactants and phosphate-based salts. Specific examples of the dispersant include, but are not limited to, at least one of nonionic surfactants, anionic surfactants, amphoteric surfactants, natural surfactants such as lecithin, and phosphates.
[0077] When the dispersant is further included, the fibrous support and the aerogel may be more uniformly dispersed in the aerogel layer.
[0078] The content of the dispersant may be 0.1% to 6% by weight, 0.1% to 5% by weight, or 0.1% to 3% by weight, based on the total weight of the aerogel layer. By including the dispersant within the above range, a battery insulation sheet having excellent heat insulation properties, compression properties, and dust resistance can be produced.
[0079] The binder and the dispersant may be included in a weight ratio of 1:0.001 to 1:0.67, 1:0.001 to 1:0.5, or 1:0.001 to 1:0.3. When the binder and the dispersant are used in combination in a weight ratio within the above range, the aerogel may be more uniformly dispersed in the aerogel layer.
[0080] In one embodiment, the fibrous support may be contained in an amount of 5 wt % to 70 wt %, the aerogel in an amount of 10 wt % to 90 wt %, and the functional material in an amount of 0.5 wt % to 20 wt %, relative to the total amount of the aerogel layer.
[0081] As an example, the aerogel layer may contain, relative to the total amount of the aerogel layer, 25% by weight to 60% by weight of the fibrous support, 30% by weight to 70% by weight of the aerogel, and 2% by weight to 15% by weight of the binder.
[0082] Specifically, the aerogel layer may contain, relative to the total amount of the aerogel layer, 30% by weight to 50% by weight of the fibrous support, 40% by weight to 60% by weight of the aerogel, and 8% by weight to 15% by weight of the binder. By forming the aerogel layer within the above ranges, it is possible to realize excellent heat insulation and improve durability at the same time, and to improve the binding force between the fibrous support and the aerogel to prevent the generation of dust.
[0083] As another example, the aerogel layer may contain, relative to the total amount of the aerogel layer, 25% by weight to 60% by weight of the fibrous support, 30% by weight to 70% by weight of the aerogel, 2% by weight to 15% by weight of the binder, and 0.1% by weight to 5% by weight of the dispersant.
[0084] Specifically, the aerogel layer may contain, relative to the total amount of the aerogel layer, 30% by weight to 50% by weight of the fibrous support, 40% by weight to 60% by weight of the aerogel, 5% by weight to 10% by weight of the binder, and 0.1% by weight to 3% by weight of the dispersant. By configuring the aerogel layer within the above ranges, it is possible to improve the dispersibility of the aerogel, realize excellent heat insulation, and improve durability at the same time, and improve the binding force between the fibrous support and the aerogel to prevent the generation of dust.
[0085] The aerogel layer may have a form in which the surface of the fibrous support is coated with aerogel. In this case, the aerogel and the fibrous support are uniformly distributed, and the binding force between the aerogel and the fibrous support is high, so that the generation of dust due to detachment of the aerogel can be reduced.
[0086] In one embodiment, the aerogel layer may be formed in a single layer structure or a multi-layer structure. When the aerogel layer is formed in a multi-layer structure, the aerogel layer may be formed in 2 to 10 layers, 2 to 7 layers, or 2 to 5 layers.
[0087] A method for manufacturing a battery insulation sheet according to an embodiment may include the steps of applying an aerogel composition onto a first substrate, laminating a second substrate onto the applied aerogel composition to manufacture a laminate, controlling a thickness of the laminate, and drying the laminate. Specifically, the method for manufacturing the battery insulation sheet may be a one-step process that does not require a separate bonding process between the substrate and the aerogel layer.
[0088] In the method for manufacturing the battery insulation sheet, the specific description of the first substrate and the second substrate may be as described above.
[0089] In the step of applying the aerogel composition onto the first substrate, the aerogel composition may be applied directly onto the first substrate.
[0090] In the step of applying the aerogel composition onto the first substrate, the first substrate may have a thin film structure having a major axis and a minor axis, and the aerogel composition may be applied in the direction of the major axis or the minor axis of the first substrate, and as a specific example, the aerogel composition may be applied in the direction of the minor axis of the first substrate. In this case, it is possible to prevent air bubbles from being generated in the aerogel layer to be formed and to control the internal porosity.
[0091] The method for producing the aerogel composition may include mixing a functional material, including a binder, a dispersant, or a combination thereof, with a solvent to produce a solvent mixture, mixing the solvent mixture with an aerogel powder to produce an aerogel mixture, and mixing the aerogel mixture with a fibrous support to produce an aerogel composition.
[0092] In an embodiment, in the step of preparing the solvent mixture by mixing the functional material with the solvent, a binder may be mixed with the solvent, or a binder and a dispersant may be mixed with the solvent. Here, the specific description of the binder and the dispersant may be as described above.
[0093] In one embodiment, the solvent may be one or more selected from the group consisting of polar solvents and non-polar solvents.
[0094] The polar solvent may include water, an alcohol-based solvent, or a combination thereof.
[0095] The water may include, for example, purified water, ultra-pure water, or a combination thereof.
[0096] The alcohol-based solvent may be, for example, one or more selected from the group consisting of methanol, ethanol, propanol, pentanol, butanol, hexanol, ethylene glycol, propylene glycol, diethylene glycol, and glycerol, but is not limited thereto.
[0097] The non-polar solvent may include a hydrocarbon solvent, for example, one or more selected from the group consisting of hexane, pentane, heptane, toluene, and benzene, and more preferably, an alkane solvent such as hexane, or a mixture containing an alkane solvent, but is not limited thereto.
[0098] The solvent may include water. When water is used as the solvent, raw material costs and post-processing costs can be effectively reduced. However, when water is used as the solvent, there is a problem that it is not easy to mix with the hydrophobic aerogel. In one embodiment, the aerogel is uniformly dispersed by controlling the mixing stage design, mixing conditions, addition and amount of binder and dispersant, etc. When the aerogel is uniformly dispersed in the composition in this way, a battery insulation sheet having excellent insulation properties, durability, and low dust properties can be formed with a thin thickness without using a large amount of binder.
[0099] The solvent may be contained in such a way that the weight ratio of the solvent to the total amount of solids in the aerogel composition is 1:1 to 1:90. For example, the weight ratio of the solvent to the total amount of solids in the aerogel composition may be 1:50 to 1:70, 1:20 to 1:30, or 1:2 to 1:10. By controlling the weight ratio of the solvent to the total amount of solids within the above range, the viscosity can be controlled and the aerogel layer can be coated.
[0100] In the step of preparing the aerogel mixture by mixing the solvent mixture and the aerogel powder, the specific description of the aerogel powder may be the same as that described above.
[0101] In the step of preparing an aerogel composition by mixing the aerogel mixture with the fibrous support, the specific description of the fibrous support may be as described above.
[0102] In each of the steps of preparing a solvent mixture by mixing a functional material including a binder, a dispersant, or a combination thereof with the solvent, preparing an aerogel mixture by mixing the solvent mixture with an aerogel powder, and preparing an aerogel composition by mixing the aerogel mixture with a fibrous support, a mixer may be used during mixing. For example, the mixer may include, but is not limited to, a planetary mixer and a thinky mixer.
[0103] As a specific example, a planetary mixer can be used to mix the solvent mixture and the aerogel powder. By mixing the solvent mixture and the aerogel powder using the planetary mixer, the aerogel powder can be uniformly dispersed in the solvent.
[0104] The planetary mixer may be a device that can be used to mix or stir different materials to produce a homogenous mixture, and may include blades that are capable of planetary motion.
[0105] In one embodiment, the planetary mixer may include one or more planetary blades and one or more high-speed dispersion blades. As a specific example, the planetary mixer may include one or more planetary blades and one or more high-speed dispersion blades.
[0106] The planetary blades and high speed dispersion blades rotate continuously about their axes, and the rotational speed may be expressed in units of rotations per minute (rpm).
[0107] In one embodiment, the planetary mixer may include a first blade and a second blade having different rotation axes. For example, the first blade may be a low-speed blade, and the second blade may be a high-speed blade. Here, low speed and high speed refer to the relative rotation speeds of the first blade and the second blade. As a specific example, the first blade may be an open blade, and the second blade may be a Despa blade.
[0108] The rotation speed of the first blade may be, for example, 10 rpm to 100 rpm, 10 rpm to 60, or 30 rpm to 70 rpm. The rotation speed of the second blade may be, for example, 100 rpm to 2000 rpm, 100 rpm to 1000 rpm, 300 rpm to 1700 rpm, or 500 rpm to 1700 rpm.
[0109] When the functional material is mixed in the solvent, the rotation speed of the first blade may be 10 rpm to 60 rpm, 20 rpm to 50 rpm, or 30 rpm to 40 rpm, and the rotation speed of the second blade may be 300 rpm to 1700 rpm, 600 rpm to 1000 rpm, or 700 rpm to 800 rpm. By mixing the solvent and the functional material as described above, a solvent mixture in which the binder, dispersant, or a combination thereof is uniformly dispersed is prepared, and aerogel mixing can be more easily performed in the subsequent step.
[0110] When mixing the solvent mixture with the aerogel powder, the rotation speed of the first blade of the mixer may be 30 rpm to 70 rpm, 40 rpm to 70 rpm, or 60 rpm to 70 rpm, and the rotation speed of the second blade may be 500 rpm to 1700 rpm, 600 rpm to 1600 rpm, or 800 rpm to 1500 rpm. By adding the aerogel powder to the solvent mixture and mixing it as described above, it is possible to prevent the aerogel powder from agglomerating with each other and induce uniform dispersion.
[0111] When mixing the aerogel mixture with the fibrous support, the rotation speed of the first blade of the mixer may be 10 rpm to 60 rpm, 20 rpm to 50 rpm, or 30 rpm to 40 rpm, and the rotation speed of the second blade may be 300 rpm to 1700 rpm, 400 rpm to 1500 rpm, or 800 rpm to 1200 rpm. When the aerogel mixture with the fibrous support is mixed in this way, the air bubbles in the composition are removed, the viscosity is adjusted, and the fibrous support is easily dispersed between the uniformly dispersed aerogel, so that the aerogel may be present in the composition in a form in which the periphery of the fibrous support is covered by the aerogel. Here, a binder is present between the aerogel and the fibrous support, which can improve the binding force between the aerogel and the fibrous support.
[0112] The step of applying the aerogel composition onto the first substrate may be carried out in a manner similar to applying a slurry onto a conventional substrate.
[0113] The step of applying the aerogel composition onto the first substrate may be repeated one or more times.
[0114] In one embodiment, the aerogel composition may further include a silane-based compound. The silane-based compound may be, for example, one or more selected from the group consisting of 3-(trimethoxysilyl)propylmethacrylate, methyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, octadecyltrimethoxysilane, ethyltriethoxysilane, and 3-glycidoxypropyltrimethoxysilane. When the silane-based compound is further included, the dispersibility may be further improved.
[0115] In one embodiment, the aerogel composition may optionally further comprise additives such as wetting agents, emulsifiers, compatibilizers, viscosity modifiers, pH modifiers, stabilizers, antioxidants, acidic or basic scavengers, metal deactivators, antifoaming agents, antistatic agents, thickeners, adhesion improvers, binders, flame retardants, impact modifiers, pigments, dyes, colorants, deodorizers, and the like.
[0116] In one embodiment, an aerogel composition is applied onto the first substrate, and a second substrate is laminated onto the applied aerogel composition to form a structure in which the first substrate, the aerogel layer, and the second substrate are laminated in sequence without the use of an adhesive.
[0117] In one embodiment, the step of controlling the thickness of the laminate may be a step of controlling the thickness of the laminate by a method of applying pressure using a roller. As a specific example, the thickness of the laminate may be controlled by passing the laminate through a gap roller having a gap thickness of a desired thickness.
[0118] In one embodiment, in the step of drying the laminate, the drying may be performed, for example, at a temperature condition of 25° C. to 100° C., 45° C. to 90° C., or 60° C. to 85° C. By drying under the above temperature conditions, a robust aerogel layer can be formed on the substrate without a separate adhesive member or bonding agent while preventing detachment of the substrate from the aerogel layer, and a coating layer can be formed in a shape in which the aerogel is coated around a plurality of dispersed fibrous supports.
[0119] In one embodiment, the steps of pressing the laminate and drying the laminate may be performed in separate steps or may be performed simultaneously.
[0120] By manufacturing a battery insulation sheet using the method according to an embodiment, a battery insulation sheet can be manufactured in a simple manner without using a separate adhesive or forming an adhesive layer, and the aerogel can be uniformly dispersed, so that the battery insulation sheet can have excellent insulation properties, durability, low dust properties, etc. even at a thin thickness.
[0121] A battery module according to one embodiment includes a plurality of cells and the battery insulation sheets respectively provided between the plurality of cells, and a first substrate and a second substrate of the insulation sheets may each be arranged to face an adjacent cell.
[0122] FIG. 2 is a schematic diagram showing a battery insulation sheet according to one embodiment formed between a plurality of cells.
[0123] 2, the battery insulation sheet 100 according to an embodiment may be formed between each of the cells 200 in a battery module including the plurality of cells 200. Here, one side of the battery insulation sheet on which the first substrate is formed and the other side on which the second substrate is formed may be disposed to face each of the adjacent cells. By forming the battery insulation sheet 100 according to an embodiment between each of the plurality of cells 200, it is possible to provide a battery module and a battery pack including the same, which are safer, by blocking a flame in advance within the cell and minimizing the spread of the flame to other cells.
[0124] Specific examples of the present invention will be presented below. However, the examples described below are merely for the purpose of specifically illustrating or explaining the present invention, and the present invention should not be limited thereto. Furthermore, since the contents not described here can be sufficiently inferred by a person skilled in the art, the description thereof will be omitted.
[0125] (Battery insulation sheet manufacturing) Example 1 1. Aerogel Composition Preparation Polyvinyl alcohol (Sigma Aldrich, Poly(vinyl alcohol)) was added as a binder to ultrapure water as a solvent, and then mixed under conditions of an open blade of 30 rpm and a despa blade of 700 rpm to produce a solvent mixture. 2Aerogel powder having a particle size of 1 / g was added and mixed at an open blade speed of 70 rpm and a Despa blade speed of 1500 rpm to produce an aerogel mixture. Glass wool was added to the aerogel mixture and mixed at an open blade speed of 30 rpm and a Despa blade speed of 1200 rpm to produce an aerogel composition. A planetary mixer (DIENTEK, PT-005) was used for mixing.
[0126] The solid content ratio of the prepared aerogel composition was confirmed to be 50 wt % aerogel, 40 wt % glass wool, and 10 wt % polyvinyl alcohol.
[0127] 2. Battery insulation sheet manufacturing The prepared aerogel composition was applied as a slurry onto a mica sheet (Famica, Muscovite) having a thickness of 0.1 mm and an air permeability of 1,000 sec / 100 cc, and then a mica sheet having a thickness of 0.1 mm was laminated in a sandwich type and coated while controlling the thickness by a roll rolling method. Then, it was dried at 60°C for 24 hours to form an aerogel layer, and a battery insulation sheet was manufactured. The total thickness of the manufactured battery insulation sheet was confirmed to be 1.48 mm.
[0128] Example 2 The aerogel composition was produced in the same manner as in Example 1, except that the amounts of raw materials added during the production of the aerogel composition were adjusted to produce an aerogel composition with a solid content ratio of 60 wt % aerogel, 25 wt % glass wool, and 15 wt % polyvinyl alcohol.
[0129] Example 3 The aerogel composition was produced in the same manner as in Example 1, except that the amounts of raw materials added during the production of the aerogel composition were adjusted to produce an aerogel composition with a solid content ratio of 65 wt % aerogel, 25 wt % glass wool, and 10 wt % polyvinyl alcohol.
[0130] Example 4 The aerogel composition was produced in the same manner as in Example 1, except that the amounts of raw materials added during the production of the aerogel composition were adjusted to produce an aerogel composition with a solid content ratio of 45 wt % aerogel, 50 wt % glass wool, and 5 wt % polyvinyl alcohol.
[0131] Example 5 The aerogel composition was produced in the same manner as in Example 1, except that the amounts of raw materials added were adjusted during the production of the aerogel composition, and the solid content ratio was 50 wt % aerogel, 49.7 wt % glass wool, and 0.3 wt % polyvinyl alcohol.
[0132] Example 6 The aerogel composition was produced in the same manner as in Example 1, except that the amounts of raw materials added during the production of the aerogel composition were adjusted to produce an aerogel composition with a solid content ratio of 40 wt % aerogel, 35 wt % glass wool, and 25 wt % polyvinyl alcohol.
[0133] Example 7 The aerogel composition was produced in the same manner as in Example 1, except that a water-dispersible polyurethane was used instead of polyvinyl alcohol as the binder in producing the aerogel composition in Example 1.
[0134] Example 8 1. Aerogel Composition Preparation Polyvinyl alcohol (Sigma Aldrich, Poly(vinyl alcohol)) as a binder and a surfactant (Triton-X100, Sigma Aldrich) as a dispersant were added to the ultrapure water solvent, and then mixed with an open blade at 30 rpm and a despa blade at 700 rpm to produce a solvent mixture. 2Aerogel powder having a particle size of 1 / g was added and mixed at an open blade speed of 70 rpm and a Despa blade speed of 1500 rpm to produce an aerogel mixture. Glass wool was added to the aerogel mixture and mixed at an open blade speed of 30 rpm and a Despa blade speed of 1200 rpm to produce an aerogel composition. A planetary mixer (DIENTEK, PT-005) was used for mixing.
[0135] The solid content ratio of the prepared aerogel composition was confirmed to be 50 wt % aerogel, 40 wt % glass wool, 9.9 wt % polyvinyl alcohol, and 0.1 wt % dispersant.
[0136] 2. Battery insulation sheet manufacturing The prepared aerogel composition was applied as a slurry onto a mica sheet (Famica, Muscovite) having a thickness of 0.1 mm and an air permeability of 1,000 sec / 100 cc, and then a mica sheet having a thickness of 0.1 mm was laminated in a sandwich type and coated while controlling the thickness by a roll rolling method. Then, it was dried at 60°C for 24 hours to form an aerogel layer, and a battery insulation sheet was manufactured. The total thickness of the manufactured battery insulation sheet was confirmed to be 1.48 mm.
[0137] Example 9 1. Aerogel Composition Preparation Polyvinyl alcohol (Sigma Aldrich, Poly(vinyl alcohol)) as a binder, water-dispersible polyurethane, and a surfactant (Triton-X100, Sigma Aldrich) as a dispersant were added to ultrapure water as a solvent, and then mixed under conditions of an open blade of 30 rpm and a despa blade of 700 rpm to prepare a solvent mixture. The solvent mixture was then measured for a BET value of 800m 2Aerogel powder having a particle size of 1 / g was added and mixed at an open blade speed of 70 rpm and a Despa blade speed of 1500 rpm to produce an aerogel mixture. Glass wool was added to the aerogel mixture and mixed at an open blade speed of 30 rpm and a Despa blade speed of 1200 rpm to produce an aerogel composition. A planetary mixer (DIENTEK, PT-005) was used for mixing.
[0138] The solid content ratio of the prepared aerogel composition was confirmed to be 50 wt % aerogel, 40 wt % glass wool, 3 wt % polyvinyl alcohol, 6.9 wt % water-dispersible polyurethane, and 0.1 wt % dispersant.
[0139] 2. Battery insulation sheet manufacturing The prepared aerogel composition was applied as a slurry onto a mica sheet (Famica, Muscovite) having a thickness of 0.1 mm and an air permeability of 1,000 sec / 100 cc, and then a mica sheet having a thickness of 0.1 mm was laminated in a sandwich type and coated while controlling the thickness by a roll rolling method. Then, it was dried at 60°C for 24 hours to form an aerogel layer, and a battery insulation sheet was manufactured. The total thickness of the manufactured battery insulation sheet was confirmed to be 1.48 mm.
[0140] Comparative Example 1 A battery insulation sheet was manufactured with a structure as shown in FIG. 3. Specifically, a 1.2 mm thick insulation layer 121 was prepared. Here, the insulation layer was formed by impregnating a glass wool blanket with an aerogel precursor at low temperature and reduced pressure, gelling the aerogel precursor, and then drying the aerogel supercritically. At this time, the composition of the insulation layer was confirmed to be 45 wt % aerogel, 45 wt % glass wool, and 10 wt % binder. Since the insulation layer manufactured in this way does not have an adhesive force of its own, a bonding process is essential for laminating the insulation layer on a substrate. Therefore, a 0.05 mm thick adhesive layer 141 was formed on each of the upper and lower surfaces of the insulation layer 121 by lamination, hot melting, or double-sided tape, and a 0.1 mm thick mica sheet was attached to each adhesive layer 141 as the first substrate 111 and the second substrate 131. At this time, the total thickness was 1.5 mm.
[0141] (Experimental Example) Experimental example 1: Thermal insulation evaluation The heat insulating properties were evaluated using the heat insulating sheets produced in the above Examples 1 to 9 and Comparative Example 1.
[0142] Specifically, each heat insulating sheet was placed between a pair of opposing 1 mm thick aluminum plates, which were then placed on a heat press, and the upper plate of the heat press was heated to 350° C., while the lower plate of the heat press was not heated and was maintained at the starting temperature of 40° C. A pressure of 20 kN was then applied to the lower plate of the heat press, and the temperature of the lower plate of the heat press after 11 minutes was measured and shown in Table 1 below.
[0143] Experimental example 2: Compression characteristic evaluation The heat insulating sheets produced in the above Examples 1 to 9 and Comparative Example 1 were used to evaluate compression characteristics.
[0144] Specifically, using UTM equipment, the 0 point was taken, and each insulation sheet was sandwiched between 1mm thick aluminum plates, and the compression rate was measured from 0kN to 80kN at a compression speed of 0.02mm / sec. Then, the thickness at 5kN and at 40kN were measured, and the reduction ratio of thickness was shown as the compression rate. The results are shown in Table 1 below.
[0145] Experimental example 3: Dustiness evaluation The heat insulating sheets produced in the above Examples 1 to 9 and Comparative Example 1 were used to evaluate dust resistance.
[0146] Specifically, the weight of each insulation sheet was measured before the evaluation. Then, the insulation sheet was placed on a rubber plate and hit with a rubber mallet at five points including the top and center of the insulation sheet, and after removing dust, the weight of the insulation sheet was measured. The weight before and after the physical impact was compared and the weight reduction rate was calculated. The results are shown in Table 1 below.
[0147] Experimental Example 4: Compressed density evaluation The heat insulating sheets produced in the above Examples 1 to 9 and Comparative Example 1 were used to evaluate the compression density.
[0148] Specifically, the mass (unit) per unit volume of each aerogel layer was measured, and the mass per unit volume (g / mm) was calculated using the thickness and area of the aerogel layer after applying pressures of 0 kN, 5 kN, 20 kN, and 40 kN vertically to the aerogel layer using the UTM equipment in the same manner as the compression characteristic evaluation method. 3 ) was calculated, and the mass per unit volume of the aerogel layer before and after compression was substituted into the above formula 1 and formula 2 to derive the values of PD1 and PD2. Here, in Comparative Example 1, the compression density evaluation was performed on the heat insulating layer. The results are shown in Table 1 below.
[0149] [Table 1]
[0150] From Table 1 above, it was confirmed that the heat insulation, dust resistance, and compression properties were all excellent in Examples 1 to 9. Here, from Examples 1 to 4, the change in heat insulation and dust resistance due to the component content of the aerogel composition can be confirmed. In addition, in Example 5, the dust resistance and compression properties were somewhat decreased due to the change in the components of the aerogel composition, but it was confirmed that the heat insulation was improved, and in Example 6, it was confirmed that the heat insulation and compression properties were somewhat decreased. In addition, in Example 7, it was confirmed that the fire-resistant binder could not play the role of a dispersant, and the dust resistance was somewhat decreased, but the heat insulation was improved. In addition, in Example 8, which is a case where a binder and a dispersant were used in combination, it was confirmed that the heat insulation, dust resistance, and compression properties were improved. In addition, from Example 9, it was confirmed that the heat insulation, dust resistance, and compression properties were further improved when polyvinyl alcohol and a water-dispersible polyurethane binder were used in combination. Furthermore, in Examples 1 to 9, the PD1 values were in the range of 0.1 to 0.5, indicating excellent durability against external impact and pressure, and the PD2 values were in the range of 0.3 to 0.8, indicating excellent durability against swelling of the internal cells.
[0151] On the other hand, it was confirmed that in Comparative Example 1, the dust resistance and durability against swelling were significantly decreased compared to the examples. In addition, when the heat insulating sheet is manufactured as in Comparative Example 1, an adhesive process is required to bond the heat insulating layer and the mica sheet using an adhesive, which increases the process cost, and since the aerogel is stuck on the blanket surface in large particle sizes, it is likely to fall off and a large amount of dust is generated. In addition, in Comparative Example 1, there is a limit to the amount of aerogel that can be added due to the manufacturing method, and there is a problem that it is difficult to add a fixed amount.
[0152] Therefore, it was confirmed that the aerogel composition according to one embodiment has excellent heat insulation properties, compression properties, and low dust properties.
[0153] Although the preferred embodiments of the present invention have been described above, the present invention is not limited thereto, and various modifications can be made within the scope of the claims, the detailed description of the invention, and the accompanying drawings, and it is to be understood that these modifications also fall within the scope of the present invention. [Explanation of symbols]
[0154] 100 Battery insulation sheet 110,111 1st base material 120 Aerogel layer 121 Insulation Layer 130,131 2nd base material 141 Adhesive layer 200 cells
Claims
1. A first substrate; an aerogel layer; A second substrate and a third substrate are laminated in this order, The battery insulation sheet, wherein both sides of the aerogel layer directly face the adjacent first substrate or the adjacent second substrate, respectively.
2. The battery insulation sheet according to claim 1 , wherein there is no other layer including an adhesive between the aerogel layer and the first substrate or the second substrate.
3. The battery insulation sheet of claim 1, wherein the aerogel layer satisfies the following formula 1: 0.1≦PD1≦0.5, PD1=PA / PB (Formula 1) (In formula 1, PA is the mass per unit volume of the aerogel layer after applying a pressure of 0 kN vertically to the aerogel layer (g / cm 3 ) and PB is the mass per unit volume of the aerogel layer after applying a pressure of 5 kN vertically to the aerogel layer (g / cm 3 ).
4. The battery insulation sheet of claim 1, wherein the aerogel layer satisfies the following formula 2: 0.1≦PD2≦0.4, PD2=PB / PC (Formula 2) (In Equation 2, P is the mass per unit volume of the aerogel layer after a pressure of 5 kN is applied vertically to the aerogel layer (g / cm 3 ), and PC is the mass per unit volume of the aerogel layer after applying a pressure of 20 kN vertically to the aerogel layer (g / cm 3 ).
5. The battery insulating sheet according to claim 1 , wherein the first substrate and the second substrate each include at least one material selected from the group consisting of a resin, a metal, and an inorganic material other than a metal.
6. The battery insulating sheet according to claim 1 , wherein the first substrate and the second substrate are each an inorganic material having an air permeability of 800 sec / 100 cc to 40,000 sec / 100 cc.
7. 2. The battery insulation sheet according to claim 1, wherein the aerogel layer comprises a fibrous support, an aerogel, and a functional material comprising a binder, a dispersant, or a combination thereof.
8. 8. The battery insulating sheet according to claim 7, wherein the fibrous support is at least one selected from the group consisting of natural fibers, silica fibers, glass fibers, ceramic fibers, carbon fibers, graphite fibers, mineral fibers, and polymer fibers.
9. The aerogel has a BET specific surface area of 500 m 2 / g to 1,000m 2 The battery insulating sheet according to claim 7, wherein the elastic modulus is 1 / g.
10. The battery insulation sheet according to claim 7 , wherein the binder comprises a water-based polymer binder.
11. The battery insulating sheet according to claim 7, wherein the dispersant is at least one selected from the group consisting of surfactants and phosphate salts.
12. The aerogel layer contains, relative to the total amount of the aerogel layer, 25% by weight to 60% by weight of the fibrous support, 30% by weight to 70% by weight of the aerogel, and 2% by weight to 15% by weight of the binder. The battery insulation sheet according to claim 7.
13. 8. The battery insulation sheet according to claim 7, wherein the aerogel layer contains, relative to the total amount of the aerogel layer, 25% by weight to 60% by weight of the fibrous support, 30% by weight to 70% by weight of the aerogel, 2% by weight to 15% by weight of the binder, and 0.1% by weight to 5% by weight of the dispersant.
14. The thickness of each of the first substrate and the second substrate is 0.01 mm to 5 mm; The battery insulation sheet according to claim 1 , wherein the aerogel layer has a thickness of 1 mm to 10 mm.
15. applying an aerogel composition onto a first substrate; forming a laminate by laminating a second substrate on the coated aerogel composition; controlling the thickness of the laminate; and drying the laminate.
16. The method for producing the aerogel composition includes: mixing a functional material, including a binder, a dispersant, or a combination thereof, with a solvent to produce a solvent mixture; mixing the solvent mixture with aerogel powder to prepare an aerogel mixture; and mixing the aerogel mixture with a fibrous support to prepare an aerogel composition.
17. The method for producing a battery insulation sheet according to claim 16, wherein the solvent is at least one selected from the group consisting of polar solvents and non-polar solvents.
18. The method for manufacturing a battery insulation sheet according to claim 15, wherein the step of controlling the thickness of the laminate comprises controlling the thickness of the laminate by a method of applying pressure using a roller.
19. The method for manufacturing a battery insulation sheet according to claim 15, wherein the step of drying the laminate is performed under a temperature condition of 25°C to 100°C.
20. A plurality of cells; and a battery insulating sheet according to any one of claims 1 to 14 provided between each of the plurality of cells; A battery module, wherein the first substrate and the second substrate of the insulation sheet are each positioned to face an adjacent cell.
Citation Information
Patent Citations
Fireproof thermal insulation material and preparation method thereof
CN112759353A
Buffering and heat-insulating composite layer, preparation method thereof, battery and power utilization device
CN114725582A
Vacuum insulation material and manufacturing method thereof
JP2006125631A
Floor structure and manufacturing method thereof
JP2019094683A
Heat insulation material and method for manufacturing the same
JP2019182728A